2013
DOI: 10.1586/ern.12.147
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychopharmacology of auditory hallucinations: insights from pharmacological functional MRI and perspectives for future research

Abstract: Experiencing auditory verbal hallucinations is a prominent symptom in schizophrenia that also occurs in subjects at enhanced risk for psychosis and in the general population. Drug treatment of auditory hallucinations is challenging, because the current understanding is limited with respect to the neural mechanisms involved, as well as how CNS drugs, such as antipsychotics, influence the subjective experience and neurophysiology of hallucinations. In this article, the authors review studies of the effect of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 121 publications
0
7
0
Order By: Relevance
“…Most importantly, research on AH in psychosis has tended to overshadow studies of the experience of hallucinations in other mental disorders, which deserve a greater focus by the research community. Similarly, whilst behavioral and physiological work on AH has made significant advances we note (Table 2) the dearth of evidence linking the cellular level of analysis to AH and inhibitory control, which warrants further investigation (Johnsen et al, 2013), as well as far too little attention to the impact of environmental/social factors on each separate unit of functioning. Indeed a challenge for future research will be to examine multiple units of analysis simultaneously, to probe the behavioral and psychological mechanisms of inhibitory control that drive the onset and persistence/severity of AH.…”
Section: Concluding Remarks Future Directions—vertical Synergymentioning
confidence: 88%
See 2 more Smart Citations
“…Most importantly, research on AH in psychosis has tended to overshadow studies of the experience of hallucinations in other mental disorders, which deserve a greater focus by the research community. Similarly, whilst behavioral and physiological work on AH has made significant advances we note (Table 2) the dearth of evidence linking the cellular level of analysis to AH and inhibitory control, which warrants further investigation (Johnsen et al, 2013), as well as far too little attention to the impact of environmental/social factors on each separate unit of functioning. Indeed a challenge for future research will be to examine multiple units of analysis simultaneously, to probe the behavioral and psychological mechanisms of inhibitory control that drive the onset and persistence/severity of AH.…”
Section: Concluding Remarks Future Directions—vertical Synergymentioning
confidence: 88%
“…Several hypotheses have been advanced that involve both the dopaminergic and glutamatergic transmitter systems. From the hypothesis advocated by Kapur and Mamo (2003) that dopaminergic transmission is dys-regulated in schizophrenia, leading to an abnormal salience to external and internal stimuli, it could be further hypothesized that AH result from an abnormal salience to inner stimuli that occur spontaneously (see also Johnsen et al, 2013). Such a hypothesis can, however not explain why the “voices” are not inhibited, only how they are initiated.…”
Section: Concluding Remarks Future Directions—vertical Synergymentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to alternative biological substrates of drug effects, a striking feature is the pharmacological heterogeneity of antipsychotics [30,33]. Moreover, there is emerging evidence from both clinical and preclinical studies suggesting differential effects among the antipsychotic drugs on non-dopaminergic, non-serotonergic drug targets suggesting that differential drug effectiveness is to be expected in clinical samples with schizophrenia [34-40]. The general lack of finding robust differences for antipsychotics may also be attributed to methodological issues, as pointed out by Leucht and collaborators [23].…”
Section: Discussionmentioning
confidence: 99%
“…Hallucinations are proposed to be caused by disturbed brain mechanisms that ineffectively distinguish self-generated mental experiences from those stimulated by external sensation ( Feinberg, 2011 ). Neuroimaging and neurophysiological studies have indicated that abnormal connectivity between frontal speech production and temporal auditory perception cortex of the left hemisphere, representing key eloquent language-related regions, may represent a mechanism for AH in schizophrenia ( Alderson-Day et al, 2015 ; Allen et al, 2012 ; Curcic-Blake et al, 2013 ; Ford et al, 2012 ; Hare et al, 2017 ; Hoffman and Hampson, 2011 ; Javitt and Sweet, 2015 ; Johnsen et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%